EXIT OF GREAT BRITAIN FROM EU: CONSEQUENCES, RISKS, OPPORTUNITIES - Kudyrko, L.P.; Kobernyk , M. V. (The actual problems of regional economy development, 2023)
Abstract. Brexit has become one of the most significant events of recent years for Europe and to the global economy as a whole. Given the importance of the UK as one of the world's largest economies and its impact on global development, the research topic is relevant, The purpose of this article is to disclose the state of affairs and assess the consequences for the economic development of the United Kingdom after its withdrawal from the European Union in the context of both the economy as a whole and its individual industries and sectors. The article uses the methods of analysis and synthesis, comparison, grouping and systematization, elements of the institutional approach, and the statistical method. Based on the data of the UK National Statistical Office and information sources of international organizations, the author identifies the consequences for the economic dynamics, labor market, and investment climate of the country. It was found that in the short term, the negative impact on economic dynamics was more significant than in subsequent years. The study showed that despite the formalization of the break with the EU, the UK remains focused on the markets of the European community and recognizes the importance of trade relations with the European Union in view of their significant impact on the country's economy. Among the obvious risks of leaving the EU is the complication of trade conditions with EU countries. There is also the possibility of an aggravation of interstate conflicts due to economic competition for strategic resources at the global level and the impact on international competition. The authors reveal the dual manifestation of Brexit's consequences in the medium term. On the one hand, a reduction in investment and the number of workers attracted to the labor market from the EU, on the other hand, an increase in the share of domestic workers in the labor market and a decrease in unemployment. Positive effects can also be assessed in terms of intensification of international economic relations outside the EU, which will ensure diversification of markets and channels of investment resources. The theoretical significance of the study is to deepen the provisions of the theory of international economic integration in terms of determining the ratio of short-term and long-term effects (static and dynamic trade effects) in the context of disintegration processes. The practical value is determined by the possibility of taking into account and empirically testing the regulatory steps of the state (on the example of the United Kingdom) to diversify foreign trade flows in order to achieve new geopolitical influence and status. Prospects for further research are seen in assessing the economic and geopolitical consequences for the UK of Ukraine's war with the Russian Federation, in view of the strong military and economic support for the Ukrainian state.